Patients' perception of their involvement in shared treatment decision making: Key factors in the treatment of inflammatory bowel disease. Issue 2 (February 2018) - Veilleux, Sophie; Noiseux, Isabelle; Lachapelle, Nathalie; Kohen, Rita; Vachon, Luc; Guay, Brian White; Bitton, Alain; Rioux, John D.; ,
Highlights: Quality of knowledge transfer between physician and patient is associated with SDM. Patient involvement in SDM is associated with higher satisfaction and lower anxiety. Involving patients in SDM in the context of IBD is important. Understanding SDM may motivate patients to be active in understanding information. Abstract: Objectives: This study aims to characterize the relationships between the quality of the information given by the physician, the involvement of the patient in shared decision making (SDM), and outcomes in terms of satisfaction and anxiety pertaining to the treatment of inflammatory bowel disease (IBD). Methods: A Web survey was conducted among 200 Canadian patients affected with IBD. The theoretical model of SDM was adjusted using path analysis. SAS software was used for all statistical analyses. Results: The quality of the knowledge transfer between the physician and the patient is significantly associated with the components of SDM: information comprehension, patient involvement and decision certainty about the chosen treatment. In return, patient involvement in SDM is significantly associated with higher satisfaction and, as a result, lower anxiety as regards treatment selection. Conclusions: This study demonstrates the importance of involving patients in shared treatment decision making in the context of IBD. Practice implications: Understanding shared decision making may motivate patients to be more active in understanding the relevant information for treatment selection, as it is related to their level of satisfaction, anxiety and adherence to treatment. This relationship should encourage physicians to promote shared decision making.